China's legal awakening : legal theory and criminal justice in Deng's era - Lu, Yonghong (Hong Kong University Press, 1995)
This book illustrates - through the analysis of more than two hundred criminal cases selected from Minzhu yu fazhi (Democracy and the Legal System) in the period 1979-89 - that the establishment of a formal criminal justice system and the development of an embryonic socialist theory of law in China reflect a genuine and widespread legal awakening.